Evaluation of the relationship between dietary acid load and cardiovascular risk factors in patients with type 2 diabetes: a case–control study - Güngör, Sedef; Saka, Mendane (Frontiers in Nutrition, 2024)
Backround: Diets high in dietary acid load are thought to be associated with metabolic diseases. However, the number of studies examining the relationship between dietary acid load and metabolic diseases in Turkey is insufficient. The aim of this study was to investigate the relationship between cardiovascular disease risk factors and dietary acid load in individuals with type 2 diabetes. Material and methods: In this case-control study, 51 participants aged 30-65 years with type 2 diabetes and 59 participants in the control group were included. Blood pressure and biochemical findings were measured. Anthropometric measurements and body composition measurements were made. Dietary intake was assessed using a 3-day (1 day on weekends, 2 days on weekdays) food consumption record. Dietary acid load scores, including potential renal acid load (PRAL) and net endogenous acid production (NEAP), were calculated based on dietary intake. NEAP and PRAL scores were categorised as low and high according to the median value. Smoking status, body mass index (BMI), systolic blood pressure (SBP), diastolic blood pressure (DBP), total cholesterol (TC), trigylceride (TG), high density lipoprotein cholesterol (HDL-C), low density lipoprotein cholesterol (LDL), waist-hip ratio (WHR), waist-to- height ratio (WtHR), hemoglobin and fat mass (%) were evaluated as cardiovascular risk factors. Results: The cut-off values of PRAL and NEAP were 3.61 and 44.78 mEq/d, respectively. After adjustment for various covariates, a significant positive association between PRAL and TG levels was observed in the diabetic group (odds ratio [OR], 5.98; 95% CI, 1.45-24.67; P = 0.013). In contrast, a negative association was found between PRAL and SBP in the control group (odds ratio [OR], 0.21; 95% CI, 0.05-0.83; P = 0.026). However, these associations were not observed for NEAP values in either group. Conslusions: A higher PRAL value was consistently associated with higher TG level, but other cardiovascular risk factors were not. More longitudinal and interventional studies are needed to better establish a causal effect between dietary acid load and cardiovascular risk factors in individuals with diabetes.